2012
DOI: 10.5812/asjsm.34724
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exercise on Urinary Gamma-Glutamyltransferase and Protein Levels in Elite Female Karate Athletes

Abstract: Purpose: Post exercise proteinuria and increased urinary Gamma-Glutamyl transferase (GGT) levels can be indicative of exercise-induced renal damage. The aim of this investigation is to study the effect of one session of intensive training on renal damage markers and compare their values to those 6 hours after training. Methods:In this cross-sectional study with pre-and post-test design, 10 elite volunteer female athletes were selected and participated in one training session (2 hours). Urine samples were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 13 publications
1
13
0
3
Order By: Relevance
“…Some literature data did not show the influence of physical effort on GGT activity changes in blood serum (13) and in the urine (1). However, other data indicate significant differences in urinary GTT level between pre-, post-, and 24 hours after training (2,31). Taking into account the proposed metabolic pathophysiological hypothesis of GGT (5), it seems that the activity of this enzyme constitutes good and, importantly, early diagnostic marker of metabolic response to the physical effort in professional and non-professional athletes' blood.…”
Section: Discussionmentioning
confidence: 99%
“…Some literature data did not show the influence of physical effort on GGT activity changes in blood serum (13) and in the urine (1). However, other data indicate significant differences in urinary GTT level between pre-, post-, and 24 hours after training (2,31). Taking into account the proposed metabolic pathophysiological hypothesis of GGT (5), it seems that the activity of this enzyme constitutes good and, importantly, early diagnostic marker of metabolic response to the physical effort in professional and non-professional athletes' blood.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the fact that sports drinks provide better intestinal absorption rates than water might explain the improved hydration status. 6,19 Shavandi et al 9 investigated proteinuria in 10 female karate athletes in three periods: before training, one hour after training, and six hours after training, and found significant increases in proteinuria one hour after training when compared to the levels before training. However, since significant differences were not identified between levels before and six hours after training, the authors concluded that karate training did not produce kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…9 It should be noted that proteinuria caused by physical exercise is a transient condition. Authors looking into the occurrence of proteinuria in other sports found that it came back to baseline levels after a few hours of rest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the presence of leukocytes (men = 43.5 % and women = 50.0 %) and erythrocytes in urine was investigated (men = 50.0 % and women = 21.7 %) [1]. A two-hour karate training session (elite athletes, female) did not result in elevated protein/creatinine ratios [33]. Moreover, the impact of different swimming distances (100, 600, 2,000 m) on proteinuria was assessed, demonstrating that the endurance distance yielded only elevated albumin levels, while the shorter distances caused an increase in the tubular marker ß2-microglobulin that gradually increased with increasing swim speed.…”
Section: Different Exercise Types and Intensities And Their Effects Omentioning
confidence: 99%